2010
DOI: 10.1016/j.ophtha.2010.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of Health-Related Quality-of-life Questionnaires in Adults Undergoing Strabismus Surgery

Abstract: Objective To evaluate the responsiveness of 2 health related quality of life (HRQOL) questionnaires, the Adult Strabismus-20 (AS-20) and National Eye Institute Visual Function Questionnaire-25 (VFQ-25), to changes in HRQOL following strabismus surgery. Design Cohort study Participants 106 adults (aged 18 to 84, median 48.5 years) undergoing strabismus surgery, 80 (75%) with diplopia and 26 (25%) without diplopia. Methods All participants completed AS-20 and VFQ-25 questionnaires pre-operatively and a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 17 publications
(24 reference statements)
6
91
2
Order By: Relevance
“…Our postoperative AS-20 score of 73 compares favourably with other authors'. Hatt et al 13,14 analysed 73 consecutive adults in a cohort study and found an average postoperative score of 78 at 6 weeks, although this did improve to 86 at 1 year. Certainly, the sizeable and statistically significant improvement in scores would support existing evidence that the psychosocial implications of strabismus are improved by surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Our postoperative AS-20 score of 73 compares favourably with other authors'. Hatt et al 13,14 analysed 73 consecutive adults in a cohort study and found an average postoperative score of 78 at 6 weeks, although this did improve to 86 at 1 year. Certainly, the sizeable and statistically significant improvement in scores would support existing evidence that the psychosocial implications of strabismus are improved by surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 lists the utilities of these complications and the source of each value. 4,6,15,16,20,33,38,42,54,57,69,70,84,92,97 Recurrence rates after each surgical strategy were estimated by meta-regression and are illustrated in Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Although the VFQ-25 identifies poorer QoL in patients with diplopic strabismus as they have more vision-related difficulties, it has a weaker discriminatory ability in non-diplopic patients. 20 This measure does, however, respond to improvements in QoL after successful surgery 20 and has excellent testeretest reliability. It is prone to ceiling effects, however, as adults with strabismus cluster towards the normal end of the range.…”
Section: Measuring Quality Of Life In Strabismusmentioning
confidence: 99%